Genetic analysis for yield and its attributes in bitter gourd (Momordica charantia) - RATHOD, VIJAYAKUMAR; BEHERA, TUSAR KANTI; MUNSHI, ANILABH DAS; JAT, GOGRAJ SINGH; VINOD, VINOD; GAIKWAD, AMBIKA B (The Indian Journal of Agricultural Sciences, 2021)
Genetic interaction and inheritance study in bitter gourd was carried out using six-generation mean analysis to determinate the types and magnitude of gene effects for yield and its attributes. The knowledge portioning to gene action and interaction, is tool for designing appropriate breeding strategy for developing varieties in bitter gourd. Four crosses, viz. DBGS-54 × DBGS-34, DBGS-2 × DBGS-34, PVGy-201 × Pusa Do Mousami and DBGS-2 × DBGS-3 were used for studying six generation (P1, P2, F1, F2, B1 and B2) model. The presence of non-allelic interaction were detected by both scaling test and joint scaling test and observed inadequacy of the additive-dominance model for all traits except vine length in cross PVGy-201 × Pusa Do Mousami.The results revealed the contribution of additive (d), dominance (h) and epistasis interaction (i, j, l) towards expression of all traits studied. In most of the characters magnitude of dominance gene effect was greater than additive gene effect suggested that recurrent selection or heterosis breeding would prove useful. Duplicate epistasis was prevalent in most of the traits like vine length, days to first female flower and fruit weight. Fruit epicarp colour and seed coat colour inheritance suggested these traits were controlled by monogenic.